HUME ON OUR GREAT PROPENSITY TO PRIDE - Barrenechea, Bihotz (ENDOXA, 2025)
Hume admits we have a great propensity to feel pride and he dedicates a lengthy treatment to its analysis. Yet his intentions in doing so are puzzling: How does pride fit into his philosophical system, and what role does it play? This paper argues that Hume found a middle ground between two divergent treatments of this passion. He criticised Hutcheson’s reliance on the moral sense and sense of honour to feel pride; and he corrected Mandeville’s insistence on pride and it’s external manifestation, honour, being the basis of morality. Hume bridged previous conceptions by making pride a “social moral sense”. Hume broadens pride’s scope beyond the virtuousness and viciousness of the passion, and depicts it as a regulatory passion on a societal level.